South-South Cooperation and the challenge of quantification, evaluation and assessment - Huitrón-Morales, Analilia (Iberoamerican Journal of Development Studies, 2016)
The emergence of a more active South-South cooperation (SSC) constitutes on of the most relevant factors for change in the International arena in the last decades. It is an expression of the new role that emerging economies of the world embody in the ensemble of the International transactions and in the generation of dynamic poles of political and economic power. However, and even if for some experts of SSC it has consolidated as a cooperation mechanism, it still faces relevant challenges in order to recognize its potentials and its benefits. One of the most discussed challenges nowadays and maybe therefore the most necessary one is quantification, evaluation and assessment of SSC actions. The lack of regional and international consensus on the mechanisms, methodologies and spaces to register, quantify and evaluate SSC hampers its positioning, further away from the rhetoric, as an effective, efficient, horizontal and sustainable tool for development in the long term. This article claims that it is still necessary to go deeper into an analysis of SSC not only from the rhetoric, but also from material elements that allow us to gain knowledge of the value of this cooperation.